Produtos de charcutaria como alternativa ao descarte de resíduos comestíveis de carauaçu (Lobotes surinamensis): avaliação sensorial e econômica - PINHEIRO, Marcus Danilo Neves (2023)
The present work aims the proportion of the development of cold cuts as an alternative to the use of edible residues. Fish processing residues. To this end, carauaçu carcasses (Lobotes surinamensis) were purchased from the GPESCA fish-processing unit. The receipt of the raw material, such as the cleaning of the carcass for the production of mechanically separated meat (CMS) and the preparation of the products was performed at the Probability Laboratory of the Federal University of Pará - Campus Bragança. After the elaboration of the CMS, three products were elaborated: bacon medallion, simple medallion and smoked medallion. As the samples were distributed to 51 untrained consumers, who in turn performed sensory evaluation, frequency of consumption and purchase, such as the economic viability of products via a nine-point hedonic scale form. Subsequently, the data were tabulated in Excel spreadsheets for further analysis related to the use of the product developed through the assignments and reviews performed by consumers. The highest acceptance rate was with the medallion containing bacon in its composition, as it has values of just over 70% in appearance, aroma, taste and texture, and the color and overall acceptance was shown with values below 70%. , the minimum required.